Preparation method of MOR type titanium silicalite molecular sieve for improving catalytic performance by introducing DDS
By introducing DDS in the hydrothermal synthesis process of MOR type titanium silicon molecular sieve, the Ti-MOR molecular sieve is modified to prepare Ti-MOR molecular sieve, which solves the problems of poor catalytic performance and complex and high cost in the prior art, and achieves significant improvement in catalytic performance and simplification of the preparation process.
Patent Information
- Application Number
- CN202510386490.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-02-27
- Filing Date
- 2025-03-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-31
AI Technical Summary
In the prior art, the catalytic performance of MOR type titanium silicon molecular sieve is not satisfactory, and the preparation process has high cost and complexity problems.
Ti-MOR molecular sieve was modified to prepare Ti-MOR molecular sieve by introducing dimethyldimethoxysilane (DDS) as an additive during the hydrothermal synthesis of MOR type titanium silicon molecular sieve. The method includes adding DDS to the gel precursor and preparing Ti-MOR molecular sieve through hydrothermal crystallization, ammonium exchange, acid treatment and gas-solid phase titanium supplementation.
The catalytic performance of Ti-MOR molecular sieve is significantly improved, the environmental pollution and cost during the preparation process is reduced, and the hydrophilicity and H2O2 enrichment ability of the molecular sieve are improved.
Smart Images

Figure CN119911924A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technology of preparing molecular sieve catalysts, and particularly relates to a method for preparing a MOR type titanium silicon molecular sieve with improved catalytic performance by introducing dimethyldimethoxysilane (DDS). Background Art
[0002] Zeolite molecular sieve is a special porous inorganic material, named because its internal pore diameter and structure can screen molecules. Zeolite molecular sieve not only has a specific pore structure, but also has adjustable acid properties, large pore volume, high specific surface area and good hydrothermal and chemical stability. It is widely used in industrial production as an adsorbent, ion exchanger and catalyst.
[0003] Since the transition metal element Ti was successfully introduced into the pure silica zeolite framework, researchers successfully prepared the titanium silicate molecular sieve TS-1 with MFI topology. The TS-1 / H2O2 system was found to perform well in many selective oxidation processes such as alcohol oxidation, phenol hydroxylation, olefin epoxidation, ketone ammoximation, etc. It is green and environmentally friendly and has high product selectivity. Because it can be widely used in the chemical industry, TS-1 has gradually become one of the most representative heteroatom molecular sieves. With the maturity of artificial zeolite technology, titanium silicate molecular sieves of other topological structures have also been synthesized, and heteroatom molecular sieves with new catalytic properties have been obtained. Various types of titanium silicate molecular sieves can be divided into TS-1, Ti-Beta, Ti-MOR, ITQ-7, Ti-MWW with microporous structure and Ti-MCM-41, Ti-SBA-15 and Ti-HMS with mesoporous structure according to the pore size.
[0004] Among them, for the synthesis of MOR-type titanium silicalite, the traditional hydrothermal method of directly introducing titanium has the following problems: the high alkalinity and high aluminum concentration required in the synthesis process of MOR itself greatly affect the state and content of titanium species in the titanium-containing mercerized molecular sieve synthesized by the in-situ hydrothermal method, making its catalytic performance unsatisfactory; the presence of skeleton aluminum species aggravates the ineffective decomposition of hydrogen peroxide on the catalyst, further affecting the catalytic activity of the catalyst, and the synthesis system of high-silicon mercerized molecular sieves often has higher costs and complexity.
[0005] Therefore, Kraushar et al. first proposed a method of implanting heteroatom Ti through post-treatment of MOR molecular sieves: the first step is to treat the MOR precursor with acid, and the second step is to implant titanium atoms through a gas phase method using TiCl4 as a Ti source or a liquid phase method using (NH4)2TiF6 as a Ti source. Compared with the direct synthesis method, the post-treatment synthesis method can synthesize the precursor MOR through a structure-free directing agent method, which can greatly reduce production costs and avoid environmental pollution problems caused by calcination to remove the structure directing agent; acid treatment can controllably remove aluminum species, effectively inhibit the formation of non-framework Ti, and more effectively implant titanium into the molecular sieve framework. The post-treatment method is currently the main way to prepare high-activity Ti-MOR molecular sieves.
[0006] However, the catalytic performance of Ti-MOR molecular sieves prepared by post-treatment using MOR synthesized in certain systems as the matrix is not satisfactory, and there is still room for improvement. The preparation of MOR-type titanium silicon molecules with higher catalytic activity has always been a key issue in scientific and industrial research.
[0007] Therefore, it is necessary to propose new catalyst modification technologies to solve the above problems. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a MOR type titanium silicon molecular sieve with improved catalytic performance by introducing DDS.
[0009] To solve the technical problem, the solution of the present invention is:
[0010] Provided is a method for preparing a MOR type titanium silicon molecular sieve with improved catalytic performance by introducing DDS, comprising the following steps:
[0011] (1) taking a silicon source, an aluminum source, potassium hydroxide, water and dimethyldimethoxysilane (DDS) as an additive, mixing and stirring at room temperature to obtain a gel precursor for synthesizing a Ti-MOR molecular sieve precursor;
[0012] Controlling the addition amount of each raw material so that the molar ratio of SiO2: Al2O3: KOH: additive: H2O in the gel precursor is 1: 0.042~0.083: 0.53~0.78: 0.05~0.20: 12~20;
[0013] (2) The gel precursor and an appropriate amount of MOR seed crystals are placed in a hydrothermal crystallization reactor to carry out a crystallization reaction; after the reaction is completed, the separated solid is washed and dried to obtain K + Type MOR precursor powder;
[0014] (3) K + The MOR precursor powder was mixed with an appropriate amount of ammonium chloride solution to perform ammonium exchange; the ammonium exchange was repeated three times, and after washing, drying, and calcination, H + Type MOR;
[0015] (4) H + The type MOR is mixed with nitric acid and treated with acid to remove part of the aluminum in the framework; after washing to neutrality, it is dried and calcined to obtain a dealuminated MOR precursor with defect sites;
[0016] (5) The dealuminated MOR precursor is placed in a quartz tube and pretreated with flowing hot nitrogen. The heated TiCl4 is then carried by flowing nitrogen to flow through the dealuminated MOR precursor to achieve contact, and titanium atoms are implanted in the dealuminated MOR precursor through a gas-solid phase reaction. The titanium-added MOR precursor powder is washed to neutrality, and after drying and calcination, a Ti-MOR molecular sieve is obtained.
[0017] As a preferred embodiment of the present invention, in step (1), the aluminum source is aluminum sulfate 18-hydrate; and the silicon source is silica sol with a solid content of 40%, and the ratio is in mass percentage.
[0018] As a preferred embodiment of the present invention, in the step (1), the stirring time during mixing at room temperature is 2 hours.
[0019] As a preferred embodiment of the present invention, in step (2), the mass ratio of the MOR seed crystal to the mass ratio of SiO2 in the gel precursor is 1:200; the temperature of the crystallization reaction is 180°C and the time is 96h.
[0020] As a preferred embodiment of the present invention, in the step (3), the concentration of the ammonium chloride solution is 1-1.5 mol / L, the solid-liquid ratio of the MOR precursor powder to the ammonium chloride solution is 1:100, the ammonium exchange temperature is 80°C, and the ammonium exchange is considered to be complete when the sodium oxide content in 0.01 g of the molecular sieve is ≤1000 ppm; the drying temperature after the ammonium exchange is 80°C until drying; the calcination temperature is 550-600°C, and the time is 6-10 hours.
[0021] As a preferred embodiment of the present invention, in the step (4), the concentration of nitric acid is 6-10 mol / L, the solid-liquid ratio of MOR to nitric acid is 1:20, the acid treatment time is 20 hours, the temperature is 80°C; the drying temperature is 80°C until drying; the calcination temperature is 550-600°C, and the time is 4-8 hours.
[0022] As a preferred embodiment of the present invention, in the step (4), when the silicon-to-aluminum ratio of the dealuminated sample is lower than 50, the operation of removing aluminum by acid treatment is repeated until the silicon-to-aluminum ratio of the sample is greater than or equal to 50.
[0023] As a preferred embodiment of the present invention, in the step (5), TiCl4 is placed in a bubbling bottle and heated, so that nitrogen passes through the bubbling bottle and carries TiCl4 into the quartz tube; the flow rate of the nitrogen is controlled to be 30-60 mL / min, and the heating temperature of the TiCl4 in the bubbling bottle is 40°C-80°C.
[0024] As a preferred embodiment of the present invention, in step (5), the temperature of the gas-solid phase reaction in the quartz tube is controlled to be 400-550°C for 6-15 hours; the temperature during calcination is controlled to be 550-600°C for 4-8 hours.
[0025] Description of the invention principle:
[0026] In the gas-solid phase preparation of MOR-type titanium silicon molecular sieves, the activity of the molecular sieve catalyst is affected by the nitrogen flow rate, treatment time and temperature during the titanium supplementation process. The synthesis conditions, modification treatment and pretreatment conditions of the matrix have a more critical influence on the production of defect sites in the framework, which can ultimately affect the activity of the prepared Ti-MOR catalyst. Many scholars have done a lot of research on the titanium supplementation conditions in the post-treatment method and found out the optimal titanium supplementation conditions and processes suitable for the current industry. However, there is still a gap in the research on the influence of the synthesis conditions of the MOR matrix itself on the activity of the final prepared Ti-MOR catalyst, such as the selection of silicon source / aluminum source / alkali source in the MOR synthesis process, whether to use a template agent, and the modification of MOR.
[0027] Therefore, it is necessary to design the titanium-filled MOR matrix to obtain more and more effective titanium-filled defect sites. Based on this, the present invention proposes to add a class of organic silanes represented by dimethyldimethoxysilane (DDS) during the hydrothermal synthesis of MOR raw powder, which can introduce a considerable number of methyl groups into MOR. After calcination, the methyl groups are converted into hydroxyl groups or hydroxyl nests. The hydroxyl groups and hydroxyl nests are the key to titanium filling by gas-solid phase method, which is beneficial to the implantation of titanium in the subsequent titanium filling process; at the same time, the hydroxyl-rich molecular sieve has better hydrophilicity and can better enrich H2O2. Through the above innovative preparation route, the purpose of effectively improving the catalytic performance of MOR-type titanium silicon molecular sieve is finally achieved.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. In the preparation process of Ti-MOR in the present invention, no organic template is used, which has little pollution to the environment.
[0030] 2. The use of additive DDS modification in the synthesis of MOR precursor can significantly improve the catalytic performance of the resulting Ti-MOR. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD spectrum of the titanium silicon molecular sieve prepared in Example 1 of the present invention.
[0032] Figure 2 This is the FT-IR spectrum of the hydrogen-type molecular sieve prepared in Example 1 of the present invention.
[0033] Figure 3 This is the FT-IR spectrum of the molecular sieve after dealumination prepared in Example 1 of the present invention.
[0034] Figure 4 This is the FT-IR spectrum of the titanium silicate molecular sieve prepared in Example 1 of the present invention.
[0035] Figure 5 This is the XRD spectrum of the molecular sieve raw powder synthesized in Comparative Example 1.
[0036] Figure 6 This is the XRD spectrum of the molecular sieve prepared in Comparative Example 1 after dealumination.
[0037] Figure 7 This is the XRD spectrum of the titanium silicon molecular sieve prepared in Comparative Example 1.
[0038] Figure 8 This is the FT-IR spectrum of the hydrogen-type molecular sieve prepared in Comparative Example 1.
[0039] Fig. 9 This is the FT-IR spectrum of the molecular sieve prepared in Comparative Example 1 after dealumination.
[0040] Fig.10 This is the FT-IR spectrum of the titanium silicate molecular sieve prepared in Comparative Example 1. DETAILED DESCRIPTION
[0041] The technical solution and effects of the present invention are further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but the protection scope of the present invention is not limited thereto.
[0042] Part I Technical Solution of the Invention
[0043] The present invention provides a method for preparing a MOR type titanium silicon molecular sieve with improved catalytic performance by introducing DDS, comprising the following steps:
[0044] (1) taking a silicon source, an aluminum source, potassium hydroxide, water and dimethyldimethoxysilane (DDS) as an additive, mixing and stirring at room temperature to obtain a gel precursor for synthesizing a Ti-MOR molecular sieve precursor;
[0045] The addition amount of each raw material is controlled so that the molar ratio of SiO2: Al2O3: KOH: additive: H2O in the gel precursor is 1: 0.042~0.083: 0.53~0.78: 0.05~0.20: 12~20; optionally, the aluminum source is aluminum sulfate 18hydrate; the silicon source is silica sol with a solid content of 40%, and the ratio is mass percentage; the stirring time during mixing at room temperature is 2 hours.
[0046] (2) The gel precursor and an appropriate amount of MOR seed crystals were placed in a hydrothermal crystallization reactor for crystallization reaction; the mass ratio of the MOR seed crystals to the SiO2 in the gel precursor was 1:200; the crystallization reaction temperature was 180°C and the time was 96h; after the reaction was completed, the separated solid was washed and dried to obtain K + Type MOR precursor powder;
[0047] (3) K + The type MOR precursor powder is mixed with an appropriate amount of ammonium chloride solution to perform ammonium exchange; the ammonium exchange is repeated three times, and the ammonium exchange is considered to be completed when the sodium oxide content in 0.01g of molecular sieve is ≤1000ppm; after washing, drying and calcination, H + type MOR; optionally, the concentration of ammonium chloride solution is 1~1.5mol / L, the solid-liquid ratio of MOR precursor powder to ammonium chloride solution is 1:100, the ammonium exchange temperature is 80℃; the drying temperature is 80℃ until drying; the calcination temperature is 550~600℃, and the time is 6~10h.
[0048] (4) H + The type MOR is mixed with nitric acid and treated with acid to remove part of the aluminum in the framework; after washing to neutrality, it is dried and calcined to obtain a dealuminated type MOR precursor with defect sites; when the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation is repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50. Optionally, the nitric acid concentration is 6-10 mol / L, the solid-liquid ratio of MOR to nitric acid is 1:20, the acid treatment time is 20 hours, the temperature is 80°C; the drying temperature is 80°C until drying; the calcination temperature is 550-600°C, and the time is 4-8h.
[0049] (5) The dealuminated MOR precursor is placed in a quartz tube and pretreated with flowing hot nitrogen. Then, the heated TiCl4 is carried by flowing nitrogen through the dealuminated MOR precursor to achieve contact. Specifically, TiCl4 is placed in a bubbling bottle and heated, so that nitrogen passes through the bubbling bottle and carries TiCl4 into the quartz tube. The flow rate of nitrogen is controlled to be 30-60 mL / min, and the heating temperature of TiCl4 in the bubbling bottle is 40°C-80°C. Titanium atoms are implanted in the dealuminated MOR precursor by gas-solid phase reaction, and the MOR precursor powder after titanium addition is washed to neutrality. After drying and calcination, a Ti-MOR molecular sieve is obtained. Optionally, the temperature of the gas-solid phase reaction in the quartz tube is controlled to be 400-550°C, and the time is 6-15 hours; the temperature during calcination is 550°C-600°C, and the time is 4-8 hours.
[0050] Part II Examples and Comparative Examples
[0051] Embodiment 1:
[0052] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C for 6 hours at 550°C, and finally purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0053] The XRD pattern of Ti-MOR is as follows Figure 1 As shown, the FT-IR spectrum of H-MOR is as follows Figure 2 As shown, the FT-IR spectrum of dealuminated MOR is as follows Figure 3 The FT-IR spectrum of Ti-MOR is shown in Figure 4 shown.
[0054] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.32%, and the selectivity of cyclohexanone oxime was 93.26%.
[0055] Embodiment 2:
[0056] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.10:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0057] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 95.48%, and the selectivity of cyclohexanone oxime was 92.44%.
[0058] Embodiment 3:
[0059] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0060] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 91.99%, and the selectivity of cyclohexanone oxime was 91.51%.
[0061] Embodiment 4:
[0062] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.050:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is subjected to ammonium exchange treatment three times at 80°C using 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, H-MOR is obtained by calcining at 550°C for 6 hours. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0063] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 50.47%, and the selectivity of cyclohexanone oxime was 85.84%.
[0064] Embodiment 5:
[0065] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.083:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0066] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 52.04%, and the selectivity of cyclohexanone oxime was 82.73%.
[0067] Embodiment 6:
[0068] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.53:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0069] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 85.37%, and the selectivity of cyclohexanone oxime was 94.38%.
[0070] Example 7
[0071] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.62:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is subjected to ammonium exchange treatment three times at 80°C using 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, H-MOR is obtained by calcining at 550°C for 6 hours. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0072] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 79.86%, and the selectivity of cyclohexanone oxime was 94.33%.
[0073] Embodiment 8:
[0074] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:12. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is subjected to ammonium exchange treatment three times at 80°C using 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0075] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 42.23%, and the selectivity of cyclohexanone oxime was 83.91%.
[0076] Example 9
[0077] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:16. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0078] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 48.80%, and the selectivity of cyclohexanone oxime was 90.47%.
[0079] Embodiment 10:
[0080] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1.5mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C for 6 hours at 550°C, and finally purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0081] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 49.73%, and the selectivity of cyclohexanone oxime was 87.48%.
[0082] Embodiment 11:
[0083] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1.2mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C for 6 hours at 550°C, and finally purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0084] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 54.26%, and the selectivity of cyclohexanone oxime was 86.62%.
[0085] Embodiment 12:
[0086] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 6 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, nitrogen purge is used for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0087] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 65.84%, and the selectivity of cyclohexanone oxime was 69.56%.
[0088] Embodiment 13:
[0089] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 10mol / L nitric acid at 80℃ for 20h, with a solid-liquid ratio of 1:20. After washing and drying at 80℃, it is calcined at 550℃ for 4h to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500℃ for 2h under 30ml / min nitrogen purge, then contacted with TiCl4 heated at 60℃ for 6h at 550℃, and finally purged with nitrogen for 2h. After washing and drying, the obtained sample is calcined at 550℃ for 4h to obtain Ti-MOR.
[0090] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 90.84%, and the selectivity of cyclohexanone oxime was 92.56%.
[0091] Embodiment 14:
[0092] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 45 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, nitrogen purge is used for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0093] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.45%, and the selectivity of cyclohexanone oxime was 94.25%.
[0094] Embodiment 15:
[0095] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water were mixed and stirred for 2 hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor was 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it was calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours, with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. If the silicon-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment and aluminum removal operation should be repeated until the silicon-aluminum ratio of the sample is greater than or equal to 50 (the same below). The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 60 ml / min, then contacted with TiCl4 heated at 60°C for 6 hours at 550°C, and finally purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0096] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 93.31%, and the selectivity of cyclohexanone oxime was 94.25%.
[0097] Embodiment 16:
[0098] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 400°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0099] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 76.81%, and the selectivity of cyclohexanone oxime was 83.33%.
[0100] Embodiment 17:
[0101] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 500°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0102] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 86.91%, and the selectivity of cyclohexanone oxime was 91.86%.
[0103] Embodiment 18:
[0104] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.05:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 40°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 4 h to obtain Ti-MOR.
[0105] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 93.85%, and the selectivity of cyclohexanone oxime was 92.46%.
[0106] Embodiment 19:
[0107] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.10:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 80°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. The obtained sample is washed and dried, and then calcined at 550°C for 4 h to obtain Ti-MOR.
[0108] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 95.12%, and the selectivity of cyclohexanone oxime was 93.59%.
[0109] Embodiment 20:
[0110] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is subjected to ammonium exchange treatment three times at 80°C using 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, H-MOR is obtained by calcining at 550°C for 6 hours. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 10 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0111] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 93.91%, and the selectivity of cyclohexanone oxime was 93.59%.
[0112] Embodiment 21:
[0113] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is subjected to ammonium exchange treatment three times at 80°C using 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, H-MOR is obtained by calcining at 550°C for 6 hours. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 15 hours. Finally, it is purged with nitrogen for 2 hours. The obtained sample is washed and dried, and then calcined at 550°C for 4 hours to obtain Ti-MOR.
[0114] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.92%, and the selectivity of cyclohexanone oxime was 92.73%.
[0115] Embodiment 22:
[0116] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 600°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. The obtained sample is washed and dried, and then calcined at 550°C for 4 hours to obtain Ti-MOR.
[0117] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.47%, and the selectivity of cyclohexanone oxime was 92.10%.
[0118] Embodiment 23:
[0119] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 580°C for 6 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. The obtained sample is washed and dried, and then calcined at 550°C for 4 hours to obtain Ti-MOR.
[0120] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.53%, and the selectivity of cyclohexanone oxime was 92.06%.
[0121] Embodiment 24:
[0122] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. The obtained sample is washed and dried, and then calcined at 550°C for 4 hours to obtain Ti-MOR.
[0123] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.85%, and the selectivity of cyclohexanone oxime was 94.84%.
[0124] Embodiment 25:
[0125] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 10 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. The obtained sample is washed and dried, and then calcined at 550°C for 4 hours to obtain Ti-MOR.
[0126] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.61%, and the selectivity of cyclohexanone oxime was 91.68%.
[0127] Embodiment 26:
[0128] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 600°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0129] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.38%, and the selectivity of cyclohexanone oxime was 92.64%.
[0130] Embodiment 27:
[0131] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 580°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0132] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.63%, and the selectivity of cyclohexanone oxime was 92.99%.
[0133] Embodiment 28:
[0134] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 6 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0135] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.68%, and the selectivity of cyclohexanone oxime was 91.71%.
[0136] Embodiment 29:
[0137] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 8 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 4 hours to obtain Ti-MOR.
[0138] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.85%, and the selectivity of cyclohexanone oxime was 94.39%.
[0139] Embodiment 30:
[0140] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 600°C for 4 hours to obtain Ti-MOR.
[0141] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.64%, and the selectivity of cyclohexanone oxime was 92.91%.
[0142] Embodiment 31:
[0143] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 580°C for 4 hours to obtain Ti-MOR.
[0144] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.82%, and the selectivity of cyclohexanone oxime was 93.72%.
[0145] Embodiment 32:
[0146] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 6 hours to obtain Ti-MOR.
[0147] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.33%, and the selectivity of cyclohexanone oxime was 93.00%.
[0148] Embodiment 33:
[0149] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40%, additives and water are mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2 in the gel precursor is 1:0.042:0.78:0.20:20. After adding a seed crystal with a mass ratio of 1:200 to the mass ratio of SiO2 in the gel precursor, they are loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for a crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder is obtained. It is treated with ammonium exchange three times at 80°C with a 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, it is calcined at 550°C for 8 hours to obtain H-MOR. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 hours with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 hours to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 hours under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 hours. Finally, it is purged with nitrogen for 2 hours. After washing and drying, the obtained sample is calcined at 550°C for 8 hours to obtain Ti-MOR.
[0150] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 94.81%, and the selectivity of cyclohexanone oxime was 92.10%.
[0151] Comparative Example 1
[0152] Compared with Examples 1-3, in Comparative Example 1, no additive DDS was added during the synthesis of the MOR raw powder, that is, the molecular sieve catalyst was not modified, and the other preparation processes were basically the same. The details are as follows:
[0153] At room temperature, aluminum sulfate 18hydrate, potassium hydroxide, silica sol with a solid content of 40% and water were mixed and stirred for several hours to obtain a gel precursor for synthesizing molecular sieves. The molar ratio of SiO2: Al2O3: KOH: H2O in the gel precursor was 1: 0.021: 0.78: 20. After adding 0.05g of seed crystals, they were loaded into a hydrothermal crystallization synthesis reactor and heated to 180°C for crystallization reaction for 96 hours. After cooling, washing and drying, MOR raw powder was obtained. It was ammonium exchanged three times at 80°C with 1mol / L ammonium chloride solution, with a solid-liquid ratio of 1:100. After washing again and drying at 80°C, H-MOR was obtained by calcining at 550°C for 6 hours. The sample obtained in the above steps is treated in 8 mol / L nitric acid at 80°C for 20 h with a solid-liquid ratio of 1:20. After washing and drying at 80°C, it is calcined at 550°C for 4 h to obtain dealuminated MOR. The sample obtained in the above steps is placed in a quartz tube, pretreated at 500°C for 2 h under a nitrogen purge of 30 ml / min, and then contacted with TiCl4 heated at 60°C at 550°C for 6 h. Finally, it is purged with nitrogen for 2 h. After washing and drying, the obtained sample is calcined at 550°C for 6 h to obtain Ti-MOR.
[0154] The XRD spectrum of MOR raw powder is as follows Figure 5 As shown, the XRD pattern of dealuminated MOR is as follows Figure 6 The XRD pattern of Ti-MOR is shown in Figure 7 As shown, the FT-IR spectrum of H-MOR is as follows Figure 8 As shown, the FT-IR spectrum of dealuminated MOR is as follows Fig. 9 The FT-IR spectrum of Ti-MOR is shown in Fig.10 shown.
[0155] The catalytic activity of the synthesized Ti-MOR molecular sieve was evaluated by the ammoximation reaction of cyclohexanone. The reaction conditions were: 0.12g of Ti-MOR catalyst, 0.39g of cyclohexanone, 20ml of tert-butyl alcohol, 0.45g of hydrogen peroxide with a mass concentration of 30%, and 16.8g of ammonia water. The specific process was: tert-butyl alcohol, catalyst and reactants were added to the flask in sequence, and the reaction was carried out at 60°C for 2h under stirring conditions. The reaction results measured after the reaction were: the cyclohexanone conversion rate was 38.80%, and the selectivity of cyclohexanone oxime was 69.91%.
[0156] It can be seen from the data of the accompanying drawings, comparative examples, and Examples 1-3 that the MOR powder after the introduction of DDS has good crystallinity compared with the hydrogen-type MOR; the acid treatment and titanium supplementation process do not destroy the crystallinity of the MOR sample; the MOR precursor prepared by the introduction of DDS has a peak at 3100-3700 cm in the FT-IR spectrum. -1There is a stronger peak at the 40°C, indicating that it has more hydroxyl groups or hydroxyl nests (derived from the fact that the MOR original powder has methyl groups after the introduction of DDS, and hydroxyl groups or hydroxyl nests are formed after calcination), and the acid treatment and titanium supplementation process did not destroy these hydroxyl groups or hydroxyl nests.
[0157] It can be seen from the catalytic reaction test results of each example that, compared with the Ti-MOR molecular sieve in Comparative Example 1, the introduction of DDS in Examples 1-3 enables the prepared Ti-MOR to have better cyclohexanone ammoximation reaction activity.
[0158] The above are only several embodiments of the present invention, and do not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not intended to limit the present invention. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a MOR type titanium silicon molecular sieve with improved catalytic performance by introducing DDS, characterized in that: The following steps are involved: (1) taking a silicon source, an aluminum source, potassium hydroxide, water and dimethyldimethoxysilane (DDS) as an additive, mixing and stirring at room temperature to obtain a gel precursor for synthesizing a Ti-MOR molecular sieve precursor; Controlling the addition amount of each raw material so that the molar ratio of SiO2: Al2O3: KOH: additive: H2O in the gel precursor is 1: 0.042~0.083: 0.53~0.78: 0.05~0.20: 12~20; (2) The gel precursor and an appropriate amount of MOR seed crystals are placed in a hydrothermal crystallization reactor to carry out a crystallization reaction; after the reaction is completed, the separated solid is washed and dried to obtain K + Type MOR precursor powder; (3) K + The precursor powder of MOR was mixed with an appropriate amount of ammonium chloride solution to perform ammonium exchange. The ammonium exchange was repeated three times, and after washing, drying and calcination, H + Type MOR; (4) H + The type MOR is mixed with nitric acid and treated with acid to remove part of the aluminum in the framework; after washing to neutrality, it is dried and calcined to obtain a dealuminated MOR precursor with defect sites; (5) The dealuminated MOR precursor is placed in a quartz tube and pretreated with flowing hot nitrogen. The heated TiCl4 is then carried by flowing nitrogen to flow through the dealuminated MOR precursor to achieve contact, and titanium atoms are implanted in the dealuminated MOR precursor through a gas-solid phase reaction. The titanium-added MOR precursor powder is washed to neutrality, and after drying and calcination, a Ti-MOR molecular sieve is obtained.
2. The method according to claim 1, characterized in that: In the step (1), the aluminum source is aluminum sulfate 18hydrate; the silicon source is silica sol with a solid content of 40%, and the ratio is mass percentage.
3. The method according to claim 1, characterized in that In the step (1), the stirring time during mixing at room temperature is 2 hours.
4. The method according to claim 1, characterized in that: In the step (2), the mass ratio of the MOR seed crystal to the mass ratio of SiO2 in the gel precursor is 1:200; the temperature of the crystallization reaction is 180°C and the time is 96h.
5. The method according to claim 1, characterized in that In the step (3), the concentration of the ammonium chloride solution is 1-1.5 mol / L, the solid-liquid ratio of the MOR precursor powder to the ammonium chloride solution is 1:100, the ammonium exchange temperature is 80°C, and the ammonium exchange is considered to be complete when the sodium oxide content in 0.01 g of the molecular sieve is ≤1000 ppm; the drying temperature after the ammonium exchange is 80°C until drying; the calcination temperature is 550-600°C, and the time is 6-10 hours.
6. The method according to claim 1, characterized in that In the step (4), the concentration of nitric acid is 6-10 mol / L, the solid-liquid ratio of MOR to nitric acid is 1:20, the acid treatment time is 20 hours, the temperature is 80°C; the drying temperature is 80°C until drying; the calcination temperature is 550-600°C, and the time is 4-8 hours.
7. The method according to claim 1, characterized in that In the step (4), when the silicon-to-aluminum ratio of the dealuminated sample is lower than 50, the acid treatment to remove aluminum is repeated until the silicon-to-aluminum ratio of the sample is greater than or equal to 50.
8. The method according to claim 1, characterized in that In the step (5), TiCl4 is placed in a bubbling bottle and heated, so that nitrogen passes through the bubbling bottle and carries TiCl4 into the quartz tube; the flow rate of the nitrogen is controlled to be 30-60 mL / min, and the heating temperature of the TiCl4 in the bubbling bottle is 40°C-80°C.
9. The method according to claim 1, characterized in that: In the step (5), the temperature of the gas-solid phase reaction in the quartz tube is controlled to be 400-550°C for 6-15 hours; the temperature during calcination is controlled to be 550-600°C for 4-8 hours.
Citation Information
Patent Citations
Preparation method of non-binder titaniferous mercerizing molecular sieve catalyst
CN103252252A
Method for synthesis of high silicon zeolite molecular sieve with universal gel
CN106542537A
Preparation method of titanium-containing molecular sieve, titanium-containing molecular sieve produced by method and cyclohexanone oximation reaction method
CN112744831A
Synthesis method of defective zeolite molecular sieve rich in hydroxyl nests
CN113683099A
Moisture-controllable, photocatalyst interior wall material, method for producing the same and coating composition for moisture-controllable, photocatalyst interior wall material
JP2002045650A